Restauro conservativo e mobilizzazione sociale in siti archeologici della valle dello Swat (Pakistan) - Luca M. Olivieri (Restauro Archeologico, 2016)
The 60-year presence of the Italian Archaeological Mission in Swat, has built a substantial continuity among the skilled workers from one generation to the next resulting in a working experience that is unique in this field. This experience was transformed in 2011-2014 into a model of intervention, the ACT project. In view of this experience, a specific approach in conservative restoration was designed with special reference to the materials and skills of the local workers. The need was felt to come up with a low cost type of intervention based on clear-cut methodological concepts that would allow government agencies in future to plan maintenance and restoration cycles also on a large scale, that is with an order of magnitude that the administration of cultural heritage has to cope with in Swat and in Pakistan. This model of intervention is pictured through two test cases, i.e. the Main Stupa at the site of Saidu Sharif I, and the colossal rock-carving of Jahanabad.